The Advances of Hydrosol–Gel Transition-Based Sensors - Haoyang Song; Shichao Ding; Mei Zhao; Qiongzheng Hu (Chemosensors, 2022)
Hydrogels, as a type of three-dimensional porous material, have attracted a lot of attention in the fields of drug delivery, artificial tissue engineering, and sensing. Due to their excellent biocompatibility and high sensitivity to external stimuli, they are widely used in the development of various sensors. Among them, the sensors constructed based on the sol–gel transition of target-responsive hydrogels are particularly welcome. Herein, the status of the sensors on the basis of sol–gel transition has been presented. The types of hydrogel sensors and the analytical methods in various application scenarios are illustrated. In addition, the future trends of the sensing systems based on sol–gel transition are briefly discussed.